Two New 1,1,3,3-Tetramethylguanidinium Halochromates (C5H14N3CrO3X) (X: Cl, F): Efficient Reagents for Oxidation of Organic Substrates under Solvent-Free Conditions and Microwave Irradiation - Kıvılcım Şendıl; H. Beytiye Özgün; Ebru Üstün (Journal of Chemistry)
Two new mild oxidizing agents 1,1,3,3-tetramethylguanidinium fluorochromate (TMGFC) and 1,1,3,3-tetramethylguanidinium chlorochromate (TMGCC) were prepared in high yields by reacting tetramethylguanidine with CrO3 and related acid. These reagents are suitable to oxidize various primary and secondary alcohols and oximes to the corresponding carbonyl compounds under solvent-free conditions and microwave irradiation.